The Ombudsman and his intervention in the trials of constitutionality concentrated in Colombia: Approach to a debate? (2012)
The present work carries out an approximation of the organic control of jurisdictional constitutionality in Colombia, from the characteristics of the two models originating in: diffuse control and the concentrated control. It then describes the main rules of procedure that exist in the trials concentrates of constitutionality, with a view to determining the form currently participates as the Ombudsman and propose a consistent adjustment in the transfer of all actions which have as their object the review of constitutionality of laws related to human rights, with the purpose that this necessarily yield a concept on the same.